Do schizotypy features predict cannabis problems in partnered community adults?. (May 2021) - Brown, Whitney C.; Leonard, Kenneth; Stasiewicz, Paul R.; Testa, Maria
Highlights: Predicted cannabis problems from schizotypal features with longitudinal methods. Disorganized and positive schizotypy associated with cannabis use in women. Cannabis problems associated with disorganized schizotypy features. Cannabis problems were not associated with negative and positive features of schizotypy. Abstract: Schizotypy and its associated features—negative schizotypy, disorganization, and positive schizotypy—are correlated with increased cannabis use. Yet, it is unclear whether cannabis users with schizotypy are at greater risk of developing cannabis problems. Individuals with elevated schizotypy may be particularly vulnerable to cannabis problems. It is important to understand this association given the unknown harms of chronic cannabis use. Data for these analyses were drawn from a larger investigation of cannabis use in adult romantic relationships. Participants were community adults (N = 366; M Age = 24.6, SD = 3.1) who reported regular use of cannabis. Participants completed baseline surveys measuring cannabis use frequency, problems, and schizotypy. Follow-up assessments of cannabis problems and frequency were completed 4-, 7- and 10-months post-baseline. Multiple regression was used to test the effect of schizotypy—measured using the Schizotypal Personality Questionnaire-Brief (SPQ-B, Raine & Benishay, 1995)—on cannabis use problems controlling for 30-day cannabis use. At baseline, disorganization and positive schizotypy were associated with cannabis use, primarily for women. Results revealed that with cannabis use frequency in the model, the Disorganization subscale of the SPQ-B predicted cannabis problems at baseline and all 3 follow-up assessments. Results are consistent with research suggesting that those exhibiting odd behaviors report more problematic cannabis use. Future research may further this line of inquiry with a focus on longitudinal, reciprocal relationships among schizotypy features, cannabis use, and cannabis problems.